Corporal Compassion : Animal Ethics and Philosophy of Body. - Acampora, Ralph R. (University of Pittsburgh Press, 2006)
"Corporal Compassion examines the practical applications of the somatic ethos in contexts such as laboratory experimentation and zoological exhibition, and challenges practitioners to go beyond recent reforms and look to a future beyond exploitation or total noninterference--a posthumanist culture that advocates caring in a participatory approach."--Jacket.